Treatment of Raw Dye Wastewater by Using Novel Process Ultrasonic Irradiation with Fenton Oxidation - Zou, Haiming; Wang, Yan; Ma, Wanzheng; Han, Xin (Asian Journal of Chemistry, 2015)
Treatment of raw dye wastewater mainly containing methyl orange was conducted by using Fenton oxidation and liking ultrasonic irradiation with Fenton oxidation (i.e., US-Fenton) in the present work. The effect of varying initial pH, hydrogen peroxide and ferrous species dosage on chemical oxygen demand (COD) and colour removal efficiencies was determined and the change of UV/Visible absorption spectra with reaction time was also measured to investigate the decomposition of organic chemical compounds containing aromatic rings. The results showed that enhancement effect of ultrasonic irradiation on Fenton oxidation was obvious, displaying a good synergistic effect in treating dye wastewater. When COD concentration and colour value were 3020 mg/L and 2060, respectively in the influent, those removal efficiencies were 93.7 and 95.9 % in the US-Fenton system (significantly higher than that in Fenton system) under the optimum condition including initial pH of 3, H2O2 of 6.0 mmol/L and Fe2+ of 0.8 mmol/L, electric output power of 250 W and electric frequency of 20 kHZ. Before oxidation in the US-Fenton system, the absorption spectrum of dye wastewater was characterized by three main bands including two in UV region with maximum absorption at 210 and 280 nm respectively and the other in visible region with that of 465 nm and the visible maximum absorption band disappeared after oxidation, suggesting the fragmentation of organic chemical compounds containing aromatic rings during the ultrasonic irradiation and Fenton oxidation process. These results suggest that the process linking ultrasonic irradiation with Fenton oxidation may provide an economical and effective alternative for treatment of dye wastewater or non-biodegradable industrial wastewater.